Chlorotoxin Fused to IgG-Fc Inhibits Glioblastoma Cell Motility via Receptor-Mediated Endocytosis. (5th December 2012) - Kasai, Tomonari; Nakamura, Keisuke; Vaidyanath, Arun; Chen, Ling; Sekhar, Sreeja; El-Ghlban, Samah; Okada, Masashi; Mizutani, Akifumi; Kudoh, Takayuki; Murakami, Hiroshi; Seno, Masaharu
Abstract : Chlorotoxin is a 36-amino acid peptide derived from Leiurus quinquestriatus (scorpion) venom, which has been shown to inhibit low-conductance chloride channels in colonic epithelial cells. Chlorotoxin also binds to matrix metalloproteinase-2 and other proteins on glioma cell surfaces. Glioma cells are considered to require the activation of matrix metalloproteinase-2 during invasion and migration. In this study, for targeting glioma, we designed two types of recombinant chlorotoxin fused to human IgG-Fcs with/without a hinge region. Chlorotoxin fused to IgG-Fcs was designed as a dimer of 60 kDa with a hinge region and a monomer of 30 kDa without a hinge region. The monomeric and dimeric forms of chlorotoxin inhibited cell proliferation at 300 nM and induced internalization in human glioma A172 cells. The monomer had a greater inhibitory effect than the dimer; therefore, monomeric chlorotoxin fused to IgG-Fc was multivalently displayed on the surface of bionanocapsules to develop a drug delivery system that targeted matrix metalloproteinase-2. The target-dependent internalization of bionanocapsules in A172 cells was observed when chlorotoxin was displayed on the bionanocapsules. This study indicates that chlorotoxin fused to IgG-Fcs could be useful for the active targeting of glioblastoma cells.